CULTURALLY RESPONSIVE TEACHING APPROACH TO IMPROVE THE QUESTIONING ABILITY OF JUNIOR HIGH SCHOOL STUDENTS THROUGH PBL - Indarwati, Rosi; Viyana Choyrunisa, Ratrie; Gusti Made Sanjaya, I (Fakultas Tarbiyah dan Keguruan Universitas Islam Negeri Antasari, 2024)
This research aims to investigate the effectiveness of implementing the Culturally Responsive Teaching (CRT) approach as best practice in enhancing the questioning abilities of middle school students through Problem-Based Learning (PBL). CRT is integrated with PBL to create a learning experience that is more relevant and engaging for students. This research utilizes both qualitative and quantitative methods within a classroom action research design. The sample includes 7th-grade students from SMP Negeri 5 Ponorogo as the main subjects. Data were collected through classroom observations, interviews, and surveys to evaluate changes in students' learning interests with the implementation of the CRT approach. The results are expected to provide in-depth insights into the positive impact of CRT implementation on middle school students' questioning abilities through PBL. The implications of this research include recommendations for curriculum development, teacher training, and the development of more contextual learning strategies to enhance questioning skills at the middle school level. The findings show that the CRT approach positively affects the enhancement of students' questioning abilities, marked by an increase in the number of students asking questions and achieving a target of 25% of the total class number. Keywords: Culturally Responsive Teaching, Questioning Ability, Problem-Based Learning.